Monetary Policy and the Relative Price of Durable Goods - Cantelmo, Alessandro (IMF Working Papers; Working Paper ;, 2017)
In a SVAR model of the US, the response of the relative price of durables to a monetary contraction is either flat or mildly positive. It significantly falls only if narrowly defined as the ratio between new-house and nondurables prices. These findings are rationalized via the estimation of a two-sector New-Keynesian (NK) models. Durables prices are estimated to be as sticky as nondurables, leading to a flat relative price response to a monetary shock. Conversely, house prices are estimated to be almost flexible. Such results survive several robustness checks and a three-sector extension of the NK model. These findings have implications for building two-sector NK models with durable and nondurable goods, and for the conduct of monetary policy.